INFLUENCE OF THE ANATOMICAL STRUCTURE OF THE COTTON STEM ON THE SHEDDING OF BUDS - Q.Davronov; B.Umarqulova (European Journal of Agricultural and Rural Education, 2022)
The main purpose of this study was to identify some of the causes of the fall of the fruit buds of the cotton plant, especially in the form of buds, combs and flowers. The general anatomical structure of woody stems with preserved and fallen half-elements is similar: it is rich, as it was but above, in-vessel lumens, the number of which per 1 mm2 of the area reaches 38-50 with a lumen diameter of 30 to 80 microns with a total area of 27-35% of the diameter stem.